Insulin signalling in mushroom body neurons regulates feeding behaviour in Drosophila larvae. - Noebels, J.L.; Avoli, M.; Rogawski, M.A.; Olsen, R.W.; Delgado-Escueta, A.V. (Journal of Experimental Biology, 2012)
Whereas the pivotal role of insulin signalling in cell division, growth and differentiation is well documented, its role in the regulation of neuronal function and behaviour has recently become the focus of intense investigation. The simple organization of the Drosophila larval brain and the availability of genetic tools to impair the function of insulin receptor signalling in a spatially specific manner makes Drosophila an attractive model to investigate the role of the insulin pathway in specific behaviours. Here, we show that impairment of insulin signalling in the mushroom body neurons, a structure involved in associative learning, impairs feeding behaviour in the Drosophila larva.